Catalan Wikipedia Multimedia experiences - Fort i Silvestre, Francesc Josep (Septentrio Conference Series, 2021)
I will make a chronology and description of several multimedia projects hold on Catalan Wikipedia the last 20 years. I will focus on two of my last presentations at Wikimania and CEE meeting, about radio programmes and dubbed content, with special atention to the rationale and why some people believes that multimedia content is important in the context of a minoritized language.